2000
DOI: 10.1046/j.1440-1819.2000.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of aromatherapy on chronic hemodialysis patients

Abstract: Effects of aromatherapy (odorless condition, lavender, and hiba oil) on mood and anxiety were investigated in 14 female patients who were being treated with chronic hemodialysis. A control period consisting of natural hospital smells was established before each test session, and then aromatic test conditions were systematically evaluated for odorless conditions as well as aromatic conditions containing lavender and hiba oil aromas. The effects of aromatherapy were measured using the Hamilton rating scale for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
47
4
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(67 citation statements)
references
References 4 publications
11
47
4
5
Order By: Relevance
“…Itai et al conducted a study to determine the effects of inhalation aromatherapy with lavender and Hiba on anxiety and depression of 14 dialysis patients for 6 weeks and showed that Hiba aroma significantly reduced anxiety and depression in patients, and lavender aroma resulted in a significant decrease only in the anxiety levels, which is inconsistent with the present study (38).…”
Section: Discussioncontrasting
confidence: 99%
“…Itai et al conducted a study to determine the effects of inhalation aromatherapy with lavender and Hiba on anxiety and depression of 14 dialysis patients for 6 weeks and showed that Hiba aroma significantly reduced anxiety and depression in patients, and lavender aroma resulted in a significant decrease only in the anxiety levels, which is inconsistent with the present study (38).…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding this finding, several other studies have established the positive impact of lavender oil essence on the level of anxiety (19,(27)(28)(29)(30), and these results are consistent with our study. However, a few studies have not demonstrated the same effect (31).…”
Section: Discussionsupporting
confidence: 93%
“…Tablo 1'de de görüldüğü gibi; yapılan çalışmalarda KBY hastaları yorgunluk, ağrı, kramplar, anksiyete, depresyon, uyku bozuklukları, kaşıntı gibi semptomlarla baş edebilmek ve yaşam kalitelerini artırmak için akupressure, akupunktur, homeopati, egzersiz, aromaterapi, yoga ve refleksoloji gibi diğer TAT yöntemlerine başvurmaktadırlar 13,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] . KBY olan hastaların kullandığı TAT yöntemleri;…”
Section: Kronik Böbrek Yetmezliği Hastalarının Kullandığı Tamamlayıcıunclassified